Percepciones de maestros y estudiantes sobre el uso del triplete químico en los procesos de enseñanza-aprendizaje - Lorduy, Danny José; Naranjo, Claudia Patricia (Revista Científica, 2020)
The objective of this article was to inquire into the perceptions of science teachers and students, about scientific notions, domains or obstacles about the use of the chemical triplet and jumps between the representative levels, during the chemistry teaching and learning processes. A qualitative methodology with a phenomenological approach was used. The investigation was carried out during eight weeks of the year 2019, through discussion groups to three groups of nine students and in-depth interviews with seven science teachers. A content analysis was conducted around two central categories of analysis: representations in chemistry and chemistry teaching and learning. It was found that science teachers do not have a command of the use of the chemical triplet and jumps between the representational levels, creating obstacles for the chemistry teaching and learning processes. The answers given by the students were located in three central categories: chemical notions, what chemistry to learn and why to learn chemistry. The use of the macro and symbolic level was found to understand and explain chemical phenomena of the context, related to those characteristics that they perceive. This study allows us to conclude that the students' perceptions focused on interpreting the phenomenon in terms of the formation of new substances, using imprecise and undifferentiated language to express their notions regarding chemical concepts. Furthermore, the teacher must abandon the knowledge transmission approach and become aware of the contextualization of phenomena from the chemical triplet.